If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4.7x + 51.4 = 5.8 + -6.7x Reorder the terms: 51.4 + 4.7x = 5.8 + -6.7x Solving 51.4 + 4.7x = 5.8 + -6.7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6.7x' to each side of the equation. 51.4 + 4.7x + 6.7x = 5.8 + -6.7x + 6.7x Combine like terms: 4.7x + 6.7x = 11.4x 51.4 + 11.4x = 5.8 + -6.7x + 6.7x Combine like terms: -6.7x + 6.7x = 0.0 51.4 + 11.4x = 5.8 + 0.0 51.4 + 11.4x = 5.8 Add '-51.4' to each side of the equation. 51.4 + -51.4 + 11.4x = 5.8 + -51.4 Combine like terms: 51.4 + -51.4 = 0.0 0.0 + 11.4x = 5.8 + -51.4 11.4x = 5.8 + -51.4 Combine like terms: 5.8 + -51.4 = -45.6 11.4x = -45.6 Divide each side by '11.4'. x = -4 Simplifying x = -4
| X+3x-5x=25 | | 42(6-(6/7)x)-6x(6-(6/7)x)-7/2(6-(6/7)x)^2 | | x=14(15)+230 | | x=14(0)+230 | | x=14y+230 | | 378000+4x=270000+5x | | -3b-25=-2(1+4b)+7 | | 30-11w+w^2=0 | | M=KV+KR | | 3x^1/2-2^1/2 | | 96+6y=-6y | | 19x=77 | | (5a^5/3b^6)^2 | | 9x+10=5x+8 | | e^6-8x=1188 | | 16x^2-x^4=0 | | h=-16t^2+33t+48 | | 2u-9=5(u+3) | | 3x+3y=60 | | 3sin^2(x)+2sin(x)-5=0 | | t+2*t+2=4 | | 3-3x=1-4x | | x^2-10=74 | | -1-(-3)=x | | 1-(-3)=x | | 2(3x+5)=26-(6-3x) | | 2b+3b-5=5 | | 4x-12x^2=256 | | 2.7x+45.8=13.2-13.6x | | sin(4x)=-cos(2x) | | y=0.90x+116 | | .05x+.09(3x+20000)=49480 |